PENERAPAN TERAPI RENDAM KAKI AIR HANGAT PADA LANSIA DENGAN INSOMNIA DI WILAYAH KERJA PUSKESMAS DI KOTA BEKASI - Astri Anisa; Indah Puspitasari; Meria Woro Listyorini (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2023)
Background: Insomnia is a health problem in the form of sleep disorders experienced by the elderly. Insomnia has several effects including fatigue, memory impairment, and irritability, to avoid these effects, warm water foot bath therapy can be carried out. Objective: This study aims to determine the application of warm water foot soak therapy in the elderly to reduce insomnia in the UPTD area of ​​the Bekasi Jaya Health Center and to find out the results of providing nursing care to the elderly with insomnia with a nursing process approach. Methodology: This study uses a case study method with data collection on cases by observation, interviews, documentation of nursing records and active participation. The instruments used in this study were the Insomnia Severity Index (ISI) and the Epworth Sleep Scale (ESS). Subjects: The subjects in this study were 5 elderly people aged 60-67 years who had sleep disturbances or insomnia. Results: The results of this case study can be that the application of warm water foot soak therapy which was instructed directly by the author to the subject can affect changes in the Insomnia Severity Index and Epworth Sleep Scale scales which are carried out routinely for 5 consecutive days. The results in this study show that the average Insomnia Severity Index scale before warm water foot soak therapy is 10-9 or severe insomnia and after warm water foot soak therapy is 0-2 or no insomnia, while the results in this study show an average The average Epworth Sleep Scale scale before warm water foot soak therapy is 11-7 or severe insomnia and after warm water foot soak therapy is 3-2 or mild insomnia and no insomnia. Recommend: For patients with sleep disorders or insomnia, they can apply warm water foot bath therapy independently, which is done once a day in the afternoon before going to bed.